Kontribusi Fazlur Rahman dalam Ushul Fiqh Kontemporer - Khoiruddin Nasutioan (Al-Jami'ah Research Centre, 2002)
Fazlur Rahman is one of the excellent scholars whose ideas in Islamic Studies cover many different kinds of disciplines. Due to his great contribution to the development of Islamic Studies, a number of researchers have conducted some studies on his thoughts. As far as Rahman is conducted, he paid his attention of study more seriously on Islamic law, including Islamic legal theories (usul figh). Therefore, a number of his works, either book or separate articles, discuss about usul fiqh, in which he has made some contributions. Among his contributions in contemporary ushul fiqh, the writer considers that two of them are very interesting to study. First, he offers to employ an integrative approach in studying Islamic teachings by looking at al-Qur'an and the tradition of the prophet. Second, he distinguishes nash into two: normative-universal and practice-temporal one. This article is trying to elaborate his great ideas on contemporary usul fiqh.